Influence Augmented Reality Building Space Against Mathematical Spatial Visualization Ability Class VIII Students On the Tube Material - Ani, Dea Indri; Reflina, Reflina (FKIP Universitas Muhammadiyah Tangerang, 2025)
Spatial visualization ability is very important in learning geometry of solid shapes because it allows students to imagine, manipulate, and represent three-dimensional objects, but many students still have difficulty in imagining the shape of solid shapes in mathematics learning due to the lack of learning media based on mathematical spatial visualization. This research aims To examine the impact of Augmented Reality (AR) media on spatial visualization of students' mathematical spatial visualization abilities. The study was conducted at Mts Darul Ulum Budi Agung Medan with a quantitative approach and one group pretest - posttest design. Class samples were randomly selected, namely class VIII-2, totaling 32 learners. The instruments used were test and student questionnaires response questionnaires. Data were analyzed through normality tests, homogeneity, N - Gain, and paired sample t - test. The results of the study showed that the average student score increased from 42.91 to 75.19. The t test showed a significance value of 0.000 <0.05, which means that the use of AR has a significant effect on students' spatial visualization b most students experienced an increase in the moderate category. A total of 91% of students also responded positively to AR-based learning. Thus, AR media has proven to be an effective learning alternative for improving mathematical spatial visualization skills in geometric geometry.